SEMIOTIC ANALYSIS OF LOGOS AS A MARKETING PROMOTION TOOL FOR BLOOD SERVICE ENTERPRISES - KHOMENKO, LILIYA; SAHER, LYDMILA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article conducted a comparative analysis of the blood services' logos, identified the features of their constituent elements for the new logo's development or existing logo's rebranding, and suggested ways to increase their efficiency. It was found 100 logos of various blood service establishments on the Internet, in particular on the official websites of the establishments and official pages on social networks, 43 of them – Europe (12 of them – Ukraine), 13 – Asia, 19 – South and North America, 15 – Africa, 10 – Australia and Oceania. There were explored the following aspects: symbolic and font elements in the logo, the colors used and their quantity, the main messages of identity, and regional differences. There were used general scientific analytical methods and analogies and prototypes to obtain practical results during the study. This study indicates that most blood establishments in the region are characterized by combined compositions in logos - a combination of the font with a visual component but with a fairly direct connotation. The most popular colors in the blood service are red, blue, black, and white font. Logos most often use 2 colors (except white), less often 1 or 3. The following blood service symbols are most often used: a drop of blood, heart, cross, person, and hands. There is also a circle, a crescent moon, a pelican, a star, and a butterfly. They stimulate a certain type of behavior and affect feelings. The results of this research allow to create a good separation from competitors and several times increase the marketing performance of the newly formed organization or existing. Blood service institutions can use this study's results to rebrand the organization and organizations' owners to develop the future brand's identity.
Keywords: logo; branding; blood service; corporate identity; semiotics; marketing promotion